Arrhythmia caused by a Drosophila tropomyosin mutation is revealed using a novel optical coherence tomography instrument. - Lisha Ma; Adrian Bradu; Adrian Gh Podoleanu; James W Bloor (PLoS ONE, 2010)
Dilated cardiomyopathy (DCM) is a severe cardiac condition that causes high mortality. Many genes have been confirmed to be involved in this disease. An ideal system with which to uncover disease mechanisms would be one that can measure the changes in a wide range of cardiac activities associated with mutations in specific, diversely functional cardiac genes. Such a system needs a genetically manipulable model organism that allows in vivo measurement of cardiac phenotypes and a detecting instrument capable of recording multiple phenotype parameters.With a simple heart, a transparent body surface at larval stages and available genetic tools we chose Drosophila melanogaster as our model organism and developed for it a dual en-face/Doppler optical coherence tomography (OCT) instrument capable of recording multiple aspects of heart activity, including heart contraction cycle dynamics, ostia dynamics, heartbeat rate and rhythm, speed of heart wall movement and light reflectivity of cardiomyocytes in situ. We applied this OCT instrument to a model of Tropomyosin-associated DCM established in adult Drosophila. We show that DCM pre-exists in the larval stage and is accompanied by an arrhythmia previously unidentified in this model. We also detect reduced mobility and light reflectivity of cardiomyocytes in mutants.These results demonstrate the capability of our OCT instrument to characterize in detail cardiac activity in genetic models for heart disease in Drosophila.